Dampak Desain Lingkungan Terhadap Ketahanan Kesehatan Kota (Urban Health Resilience) Kasus : Kelurahan Mojo, Surabaya - Dewi, Aurelia; Roychansyah, Muhammad Sani; Hadianti, Atrida (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
The COVID-19 pandemic has highlighted the importance of urban design planning in aggravating or reducing urban health inequalities. Health resilience must be a priority to control the impact of a health crisis. The study examines the factors that impact urban health resilience, utilizing seven indicators of the urban design element, to determine the level of urban health resilience in densely populated settlements. The study uses empirical data collection, physical analysis, and statistical calculations to determine the relationship between the urban design element and health. The findings show a strong link between urban design and urban health resilience. Implementing urban health resilience is vital to creating a healthier, more durable urban environment that can withstand future health emergencies. Therefore, focusing on health resiliency is critical for a more resilient urban environment.